THE INVOLVEMENT OF THE FATHER’S ROLE IN DEVELOPING HONESTY CHARACTERISTICS IN YOUNG CHILDREN AT AN-NAJAH ISLAMIC KINDERGARTEN JATIMULYO, SOUTH LAMPUNG: Keterlibatan ayah dalam membentuk karakter jujur pada anak usia dini dan cara cara ayah untuk terlibat dalam pembentukan karakter jujur pada anak usia dini di TK Islam An Najah Jatimulyo, Lampung Selatan - yunita, irma; Herpratiwi; Sulistianah (EDUCATE : Jurnal Teknologi Pendidikan, 2024)
Father’s involvement in shaping character in children is a must, including in forming honest character. This study aims to determine and describe fathers’ involvement in forming honest characters in early childhood at An Najah Jatimulyo Islamic Kindergarten, South Lampung. This study used a type of descriptive qualitative research. The techniques used in data collection are observation, interviews, and documentation. The informants were selected based on the results of observations of student honesty scores in the categories of less, medium, and good. The fathers of some students in this category were used as informants in interviews. The involvement of fathers in forming honest character in children is significant. Fathers must be involved in introducing and providing direction and understanding to children about the value of honesty. The involvement of fathers who are active in character building in children will provide their stimulus so that children are more optimal in applying the values of honesty in daily activities. This study’s results show that fathers’ involvement in forming honest characters in children in An Najah Jatimulyo Islamic Kindergarten is quite good.